Association between maternal depression and wheezing in preschool children - Özdoğan, Şebnem; Kurtaraner, Tuğçe; Gencer, Haşim; Kabakcı-Kaya, Dilek; Çelik-Erden, Selime (The Turkish Journal of Pediatrics, 2016)
The aim of this study was to assess whether maternal depression was associated with recurrent wheezing attacks in preschool children. A case-control study was conducted involving 51 preschool children who were hospitalized due to wheezing attacks and 50 age-matched healthy subjects. Sociodemographic characteristics of the children and their mothers were investigated. The Beck depression inventory was administered to the mothers. In the case group, the anthropometric measurements were determined to be significantly lower than in the control group (p < 0.05). The rate and severity of maternal depression were significantly higher (p < 0.05) in mothers of cases. Multivariate regression analysis indicated that male gender of the child and maternal history of asthma were significant risk factors for maternal depression (odds ratio 4.671; 95% CI 1.21-18.11 and 5.263, 95% CI 1.05-32.42, respectively). Having a male child with wheezing attacks and a history of maternal asthma were identified as important risk factors for maternal depression.